Menelisik Peran Auditor Internal Pemerintah Saat Ini Berdasarkan Penilaian Internal Audit Capability Model (IACM) - Manggarani, Yanti; Yudiyanto, Yudiyanto (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p09, 2023)
The research aims to test the effectiveness of government internal audits. This study uses multiple regression analysis techniques to determine the effectiveness of internal audit on the role of assurance and consulting. The research population is 542 local governments in Indonesia with a time span between 2018-2020. The samples taken were 1,559 local governments to test the role of assurance, while to test the effectiveness of internal audit on their consulting role, there were 1,484 local governments. The results of the study show that the more effective the Government Internal Supervisory Apparatus (APIP), the role of APIP in conducting assurance and consulting will also increase. In this study, APIP's assurance role was seen from APIP's ability to review LKPD. The consulting role for APIP will also increase when APIP is able to maintain good relations with other organizational units. Keywords: Internal Audit; Consulting; Assurance; Audit Opinion; Capability Model.